A Review on Sustainable Self-Healing Bacillus Bacterial Concrete on Water Absorption Test - Anthony, Sararossy Sungki; Mokhtar, Norfaniza (Recent Trends in Civil Engineering and Built Environment, 2024)
Concrete is an important construction materials as it can resist compressive loads. But if the load applied to the concrete exceeds its limit of resistance, the strength is reduced. Cracks might occur and treatment for cracks is quite expensive. To overcome this situation, introducing bacteria Bacillus strain was mixed with concrete, in order to produce Calcium carbonate crystals form. This can fill tiny cracks in the concrete and heal the concrete without any human intervention. The focus of this review was on the Bacillus strain bacterium cell's ability to generate Calcium carbonate to heal the crack. Concrete added with Bacillus strain is durable than conventional concrete. The properties of the added concrete should be able to self-repairing cracks without any external aid.  Hence this method is effective to heal concrete. The goal of this research is to examine the impact of the Bacillus strain that was added into concrete and the effectiveness of Bacillus strain as a self-healing agent by water absorption test with a different type of Bacillus strain, concentration, and growth medium. Through all the case study reviewed, the highest water absorption reduction is 70% with a selection of Bacillus Pasteuri, cell concentration 10^6 cells/ml, and growth nutrient is NH4-YE medium. It is proven that concrete embedded with bacteria has a lower water absorption capacity than nominal concrete.